Treatment of postoperative non-union with internal fixation loosening of Garden IV femoral neck fracture with teriparatide in a young adult: A case report - Lai, Lili; Li, Yifan; Shen, Miaoda; Wang, Xuanwei; Zhong, Cheng; Xu, Sanzhong (Frontiers in Surgery, 2022)
Background Postoperative non-union of femoral neck fracture often needs secondary operation. We report a case of a postoperative non-union of femoral neck fracture treated with teriparatide. Case presentation A young male patient with Garden IV femoral neck fracture who showed no obvious signs of healing 3 months after percutaneous hollow nail fixation in which the fracture line was enlarged and the hollow nail was withdrawn. Bone non-union healed after 6 months of continuous subcutaneous injection of teriparatide at a dosage of 20 mg/day after the patient refused a secondary surgery. As far as we know, there have been no relevant reports on this type of fracture yet. Conclusions Teriparatide is expected to be beneficial in treating young patients with a displaced femoral neck fracture who have difficulty in healing from non-union and who are keen on avoiding secondary surgery.